Application Strategies and Tips for Using the Nursing Professional Development Practice Model. Issue 4 (July 2017) - Cobb, Susan C.
Abstract : In the past year since the 3rd edition of the Nursing Professional Development: Scope and Standards of Practice was released, many Nursing Professional Development departments across the nation have incorporated this foundational document into their practice. In this column, we continue to describe the activities of our colleagues to integrate the scope and standards into practice.